Validation of QTLs for earliness and plant type traits in pigeonpea (Cajanus cajan (L.) Millsp.) - Geddam, Sekhar Babu; Raje, R.S.; Prabhu, K.V.; Singh, N.K.; Chauhan, D.A.; Jain, Priyanka; Khare, Ambika; Yadav, Rekha; Yadav, Anshika (The Indian Journal of Genetics and Plant Breeding, 2016)
Validation of QTLs recently reported in pigeonpea for plant type and earliness traits viz., plant height, number of secondary branches, number of pods per plant, days to flowering and days to maturity was carried out using RILs derived from the cross Pusa Dwarf x H2001-4. RILs exhibited significant phenotypic variation for the all the traits. Using Interval mapping analysis QTLs for these traits except for plant height were successfully validated in the RILs in the marker interval ASSR100 and ASSR 206. Contribution of enhancing alleles by female parent Pusa Dwarf for the traits was also confirmed. QTLs for earliness traits qFL5.1 and qMT5.1 explained 15.3% and 11.6% phenotypic variation respectively while QTLs for plant type characteristics qSB5.1 and qPD5.1 exhibited phenotypic variation of 18.1 % and 11.2 % respectively